Analisis Puisi “Aku Mencintaimu Diam-Diam” Karya Anwar Maulana (Sekolah Tinggi Agama Buddha Nalanda, 2023)
Poetry is a form of fiction that contains an implied meaning. Poetry can motivate writing lovers, especially readers who are interested in reading something that has meaning and meaning implied in it from a poem through analysis. Based on previous understanding or exposure, the author is interested in conducting a study, namely analyzing Anwar Maulana's poem entitled